Performance of raft foundations with settlement reducing piles - Cao, Xiaodong (2008)
As foundations for high-rise buildings, rafts have been used successfully for many years. Analyses of raft foundations subjected to working loads indicate that generally the bearing capacity requirement can be fulfilled without much difficulty but the rafts may settle excessively. Although there are several methods of controlling settlements of rafts, the most effective and economical technique may be by means of settlement reducing piles.